Perilaku Birokrasi dalam Meningkatkan Partisipasi Masyarakat (Studi tentang Pelaksanaan Pembangunan Kampung di Distrik Wasior Kabupaten Teluk Wondama) - Doran, Nurhayati; Tafalas, Muhamamd Guzali; Rulinawaty, Rulinawaty (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The study employed a qualitative method with a descriptive design. Data sources included informants’ statements and actions, as well as primary and secondary data. The data collection procedure consisted of four stages: pre-fieldwork, fieldwork, data processing, and report writing. The findings reveal that active community participation at every stage of development is a key factor in ensuring success. Nevertheless, community participation in Wasior District remains relatively low. Bureaucratic behavior has not effectively boosted participation, as indicated by suboptimal leadership, communication, and education. Moreover, coordination between the District Head and branch offices or district-level agencies has not been executed in accordance with the established work plan. Low education levels among the local population impede their ability to participate effectively. Meanwhile, the capacity-building efforts directed toward village government officials and community institutions are still not optimal. Over the past five years, development programs have predominantly been driven by higher-level governmental directives, leaving community aspirations inadequately addressed. Additionally, customary regulations regarding land ownership pose significant obstacles to the implementation of development programs and adversely affect overall community participation.